The Influence Of Social Media Marketing And E-Wom On Purchasing Decision With Trust And Brand Image As Mediating Variables On Fashion Purchases In Tiktok Shop - Lilis Karlina; Anas Hidayat (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of social media marketing and electronic word of mouth (E-WOM) on purchasing decisions for fashion products in TikTok Shop, with trust and brand image as mediating variables. The study used a quantitative approach with a population of university students in Indonesia who had shopped for fashion through TikTok Shop. Sampling was carried out using a non-probability sampling technique through convenience sampling with a total of 280 respondents. Data were collected through an online questionnaire using Google Form with a five-point Likert scale, then analyzed using the Structural Equation Modeling (SEM) method with the help of SmartPLS software. The results showed that social media marketing and E-WOM had a positive and significant effect on trust, brand image, and purchasing decisions. In addition, trust and brand image were also proven to have a positive effect on purchasing decisions. Mediation tests showed that trust was able to mediate the influence of social media marketing on purchasing decisions, while brand image mediated the influence of E-WOM on purchasing decisions. These findings indicate that online social media marketing activities play an important role in building trust and brand image that drive purchasing decisions in TikTok Shop.